2010
DOI: 10.1111/j.1439-0396.2010.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Caecum odd‐numbered and branched‐chain fatty acid composition in response to dietary changes in fattening rabbits

Abstract: The study aimed to describe the interactions between nutrition and caecal bacteria abundance using odd-numbered and branched-chain fatty acids (OBCFA). Following a 2 × 2 factorial design, 47 rabbits were fed diets with two levels of digestible fibre (DF, 180 vs. 260 g/kg DM) supplemented with soybean oil (SO, 20 g/kg) or not. At 77 days of age, fatty acid (FA) composition was determined in caecal contents. The microbial origin of OBCFA vs. dietary FA in caecal contents was illustrated by clustering of these FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, in rabbits it is not known which bacteria are involved in CLA production. Some microorganisms that metabolize FA have been detected in rabbit feces, such as Bacteroides (Papadomichelakis et al, ) and Staphylococcus (Comi and Cantoni, ). In humans, it has been observed that Lactobacillus , Bifidobacterium , Propionibacterium , Eubacterium , Roseburia , and Butyrivibrio are involved in the production of CLA isomers in the large intestine (Devillard et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in rabbits it is not known which bacteria are involved in CLA production. Some microorganisms that metabolize FA have been detected in rabbit feces, such as Bacteroides (Papadomichelakis et al, ) and Staphylococcus (Comi and Cantoni, ). In humans, it has been observed that Lactobacillus , Bifidobacterium , Propionibacterium , Eubacterium , Roseburia , and Butyrivibrio are involved in the production of CLA isomers in the large intestine (Devillard et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in the cecum of rabbits play an important role in the production of protein (Belenguer et al, ), vitamins (Hörnicke, ), and volatile FA (Amici et al, ; Xiccato et al, ). Bacteria in the cecum also modify FA and contribute to PUFA synthesis from the dietary intake of linoleic and linolenic acids (Amici et al, ; Bauman et al, ; Papadomichelakis et al, ). In ruminants, the microorganisms that metabolize FA include Ruminococcus , Fusocillus , and Anaerovibrio (Hobson and Stewart, ); Propionobacterium can produce CLA trans ‐10, cis ‐12 (Castillo et al, ), whereas Butyrivibrio can produce CLA cis ‐9, trans ‐11 (Wallace et al, ).…”
Section: Discussionmentioning
confidence: 99%